Evaluation of two prostaglandin products in pregnant sows for initiation of luteolysis - Evans, E.I.; Stevenson, Jeffrey S.; Davis, Duane L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used 66 pregnant sows to compare serum progesterone concentrations following a single injection of either saline or one of two prostaglandin F2a products approved for use in swine. Pregnant sows in a commercial swine farm were assigned to one of the three groups in a completely randomized design balanced across treatment for parity and day of gestation. Each sow received a single intramuscular dose (2 mL) on d 111, 112, or 113 of gestation. Mean serum progesterone concentrations were decreased significantly at 6 and 12 hours after dose administration of both prostaglandin products. However, these effects did not differ. Serum progesterone concentrations did not decrease significantly at any time in the control group. This indicates that regression of corpora lutea was initiated at the same time by both prostaglandin products.
Keywords: Swine; Pregnant sows; Prostaglandins; Luteolysis